Photochemistry A Modern Theoretical Perspective - Persico, Maurizio (Theoretical Chemistry and Computational Modelling,, 2018)
This book offers an introduction to photochemistry for students with a minimal background in physical chemistry and molecular quantum mechanics. The focus is from a theoretical perspective and highlights excited state dynamics. The authors, experienced lecturers, describe the main concepts in photochemical and photophysical processes that are used as a basis to interpret classical steady-state experimental results (essentially product branching ratios and quantum yields) and the most advanced time-resolved techniques. A significant portion of the content is devoted to the computational techniques present in quantum chemistry and molecular dynamics. With its short summaries, questions and exercises, this book is aimed at graduate students, while its theoretical focus differentiates it from most introductory textbooks on photochemistry.